Pemodelan Spasial Prevalensi Ketidakcukupan Konsumsi Pangan Menggunakan Pendekatan Ketahanan Pangan di Indonesia Tahun 2022 - Yahya, Muhammad Gozali; Utami, Intan Putri; Ariansyah, Setiawan (Politeknik Statistika STIS, 2023)
The prevalence of undernourishment (PoU) is one of the strategic indicators in achieving SDG Goal 2, which is zero hunger. The percentage of the population experiencing undernourishment in Indonesia has been increasing over the past three years. In 2020, 8.34% of the population experienced undernourishment. This number slowly rose to 8.49% in 2021 and sharply increased to 10.21% in 2022. Based on these findings, this research aims to identify patterns and factors influencing PoU. The distribution of PoU values among provinces shows a tendency of similarity in values among neighboring provinces. Based on the Spatial Durbin Model (SDM) regression analysis, it is known that significant variables affecting the prevalence of undernourishment are population density in the availability dimension, open unemployment rate and percentage of good roads in the access dimension, life expectancy at birth in the utilization dimension, as well as economic growth and average rainfall in the stability dimension.